Integration of Contraceptive Services Into Anticoagulation Management Services Improves Access to Long-acting Reversible Contraception. Issue 2 (February 2019) - Bernard, Caitlin; Pekny, Chelsea; Omukagah, Christabell O.; Bernard, Christian O.; Manji, Imran; Pastakia, Sonak D.; Christoffersen-Deb, Astrid
Abstract : (Abstracted from Contraception 2018;98(6):486–491) Increasing access to contraception in women of reproductive age is a cost-effective strategy to reduce maternal morbidity and mortality, especially in women with chronic diseases. Approximately 28% of global maternal mortality is nonobstetric in nature, and 70% of these cases are due to preexisting medical conditions exacerbated by pregnancy.